Pharmacologycal activity of peperina (Minthostachys verticillata) on gastrointestinal tract - Rodríguez Basso, Angeles; Carranza, A.; Zainutti, V.M.; Bach, Hernán Gerónimo; Gorzalczany, S.B. (Elsevier, 2022)
Ethnopharmacological relevance: Minthostachys verticillata (Griseb.) Epling (Lamiaceae), known as Peperina is a medicinal native plant, with a traditional use as a digestive, antispasmodic and antidiarrheic. Aim Of The Study: Despite its folkloric use, no scientific evaluation of this plant related to the astrointestinal inflammatory process has been carried out to date. The present study aims to assess the effects of M. verticillata on gastrointestinal system in experimental models. Materials and methods: M. verticillata (250 and 500 mg/kg) was orally tested in a colitis model induced by acetic acid. Colon weight/length ratio, oxidative stress (oxidized and reduced glutathione), histological changes using Alcian blue and hematoxylin & eosin staining and expression of IL1β, TNFα, iNOS, COX-2 were evaluated. The effect of the extract in three additional in vivo models were studied: intestinal motility and diarrhea induced by ricin oil, and visceral pain induced by intracolonic administration of capsaicin. Finally, the activity on con centration response curves of acetylcholine, calcium chloride, potassium and serotonin were achieved in isolated rat jejunum. Results: In the colitis model, M. verticillata induced a significant reduction in the colon weight/length ratio, oxidative stress and expression levels of IL-1β, iNOS and COX-2. Also, the extract diminished the severity of microscopic tissue damage and showed protective effect on goblet cells. Intestinal motility, diarrhea, visceral pain-related behaviors and referred hyperalgesia were significantly reduced when the animals were treated with the extract. Furthermore, in isolated jejunum, M. verticillata significantly reduced the contraction induced by serotonin and acetylcholine. Likewise, the extract non-competitively inhibited the response-concentration induced by CaCl2 and inhibited both low and high K+-induced contractions. Conclusions: This is the first study to validate traditional use of M. verticillata for digestive disorders and demonstrated that its aqueous extract could represent a promising strategy in targeting the multifactorial pathophysiology of inflammatory bowel disease.